2021
DOI: 10.1111/wvn.12505
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Acceptability of a Language Concordant Health Coaching Intervention Delivered by Nurses for Latinx With Type 2 Diabetes

Abstract: Background: Latinx immigrants have high rates of type 2 diabetes (T2D), exhibit out-of-range glycemic control, and have higher rates of diabetes-related complications than non-Latinx whites, with limited English proficiency (LEP) being a major barrier to care. Aims:We tested the feasibility and acceptability of a language concordant (provider that is proficient in the patient's preferred language) health coaching intervention delivered by nurse and nurse practitioner students in a pilot study of Latinx immigra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Of these, three studies focused on low-income individuals 16,37,40 and three studies recruited from Latinx and/or African American populations. 32,36,37 Two studies also reported occupation-specific study populations; one study was conducted among veterans 44 and another among manual labourers. 39 In addition to T2D, three studies focused on populations with comorbidities, 16,33,44 including obesity 16 and hypertension.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, three studies focused on low-income individuals 16,37,40 and three studies recruited from Latinx and/or African American populations. 32,36,37 Two studies also reported occupation-specific study populations; one study was conducted among veterans 44 and another among manual labourers. 39 In addition to T2D, three studies focused on populations with comorbidities, 16,33,44 including obesity 16 and hypertension.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…hospital clinics), 20,22,[25][26][27][28]37,43 six interventions were delivered through a community health setting (i.e. community health centres, public health clinics and patient homes), 21,27,32,35,36,40 and three interventions were delivered through non-healthcare sites (i.e. libraries, research offices and churches).…”
Section: Adoptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, diabetes is considered as one of the most common chronic diseases. 1 Insufficient insulin secretion or insulin resistance in the human body causes metabolic disorders and cannot properly regulate blood glucose levels. 2,3 With the improvement of living standards, the acquisition of refined foods has become easier, but people's health awareness has not significantly improved.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, diabetes is considered as one of the most common chronic diseases 1 . Insufficient insulin secretion or insulin resistance in the human body causes metabolic disorders and cannot properly regulate blood glucose levels 2,3 .…”
Section: Introductionmentioning
confidence: 99%